THE USE OF GROWTH FACTORS IN PERIODONTITIS TREATMENT - V. P. Mudrov; V. N. Nelyubin; E. S. Vorobieva; E. Yu. Lysiuk; M. S. Miandiev; I. S. Fomenkov; S. Yu. Ivanov (Медицинская иммунология, 2018)
Periodontal disease, including gum disease, gingivitis, periodontitis and periodontal disease is frequently associated with progressive loss of bone and soft periodontal tissues. Recent studies suggest effectiveness of platelet-derived growth factor, fibroblast growth factor and other growth factors, which may stimulate regeneration of connective and bone tissue. A number of cytokines and growth factors participate in regulation of angiogenesis, but vascular endothelial growth factor (VEGF) is the most powerful agent, acting directly on the vascular endothelium. VEGF detected in saliva and endothelial cells of periodontium. VEGF plays a dominant role both in periodontal health maintenance as well as in chronic inflammatory periodontal disease. The aim of this work was to develop implementation of VEGF in periodontology, and a search for laboratory markers of therapeutic efficiency in periodontitis. We observed 19 patients aged 53-79 years with I-II grade periodontitis. In frames of periodontal therapy, the patients used a drug “Rebon. Gel for Gum” (“GF group”, Russia). The drug represents a composition of bioresorbable carbohydrates on the basis of carboxymethylcellulose, forming the cellular basis for similar extraclean matrix. It contains different sodium, potassium, phosphorus, chlorine salts in order to balance the tissue pH, and a complex of glycated recombinant polypeptides identical to cytokines and human growth factors. ELISA method was used in the biological samples for detection of VEGF, human isoform A-165 (“SCI store” Ltd., Russia), and IFNγ (JSC “Vector Best”, Russia). All our patients noted a decrease in pain after the treatment, as well as a significant acceleration of healing processes in oral cavity. Observation of the oral cavity state showed good dynamics and acceleration of bone tissue regeneration. After the treatment course, the level of IFNγ increased from 14.48 to 27.45 pg/ml. The difference before and after treatment values was significant (p = 0.022), despite a sufficient range of measured values. VEGF in gingival fluid showed a large scatter of values, from 26 to 279 pg/ml before treatment, and 16 to 198 pg/ml after treatment. Generally, a tendency for VEGF decrease was observed after treatment. To diagnose the current state of the periodontium, an importance of analyses of the gingival sulcus fluid is actual. The developed diagnostic approaches based on measuring the IFNγ, VEGF levels in screening and monitoring regimens help to provide a more effective treatment. Introduction of a complex preparation with growth factors and peptidoglycan-recognizing protein seems to accelerate epithelialization and regeneration of connective and bone tissue.